Radical right populist politics in Hungary: Reinventing the Magyars through sport - Molnar, G.; Whigham, S. (International Review for the Sociology of Sport, 2021)
Given the contemporary growth of `populist` political parties and movements in a number of highly developed democratic states in Europe and North America, there has been a resurgence in academic interest around the various causes for the groundswell of support for political populism. Given this broader political context, this paper explores the interconnection between sport and populist politics in Hungary, with a particular emphasis on the appropriation of sport by `right-wing` populist political actors. In particular, this paper will examine the politics-sport interconnection by discussing how the Prime Minister of Hungary, Victor Orbán, uses football, and sport more broadly, and the ways in which the Hungarian government have attempted to reinvent a strong nation and national identity through sport and related political populism. These attempts have been influenced by the interaction between forces of Westernisation and the country`s continuing post-communist transition, with the view to (re)inventing the Hungarian nation.